(untitled) (Journal of Dhaka Medical College, 2021)
Acute heart failure is one of the common causes of morbidity & mortality among the patients admitted in hospital. This prospective observational study was done to characterize sociodemographic, clinical & laboratory characteristics with short clinical outcome. Total 110 patients of acute heart failure were included in this study where mean age was 53.88 (± 14.6) years. Majority of the patients were aged between 51-60 years 35 (32%). 79(72%) of them smoker and 12(11%) were alcoholic. Major comorbidities were hypertension 59 (53.63%), ischemic heart disease 42 (38.18%), DM 39(35.45%), chronic kidney disease 25(22.72%). Most common symptoms at presentation were shortness of breath110(100%) along with palpitation 96(87.27%), orthopnea 85(77.27%), paroxysmal nocturnal dyspnea 59(53.63%), ankle edema 71(64.54%), raised JVP 75(68.18%), bilateral basal crepitation on auscultation 80(72.72%), anemia 19 (17.27%) & oliguria 23(20.90%) where mean duration of symptoms was 11 ± 2 days. Lab investigations revealed decreased Hemoglobin (10.71 ± 1.49) g/dl, proteinuria in 31 (28.18%), ketone body 5 (4.5%), raised creatinine in 23(20.93%), hyponatremia 38 (34.54%), hypernatremia 6 (5.45%), hypokalemia 6 (5.45%), hyperkalemia 3 (2.72%). Regarding cardiac events 37(33.63%) encounter myocardial infarction, cardiogenic shock 29(26.36%), Cardiac arrhythmia 27 (24.5%), cardiac arrest 6 (5.45%), non-cardiac events like stroke 6(5.45%), hyperosmolar hyperglycemic state 2(1.8%), diabetic ketoacidosis 5(5.45%), acute kidney injury 23(20.90%). However, among cardiac arrhythmia atrial fibrillation found 13(11.81%) followed by multiple ventricular ectopic 12 (10.90%), ventricular tachycardia 7 (6.36%), Complete heart block 6 (5.45%), variable heart block 4 (3.63%), long QT 2(1.8%). Regarding short clinical outcome 52(47.27%) were improved, 40 (36.36%) had persistent symptoms & rest 18 (16.36%) expired. Most common causes of those deceased person were cardiogenic shock 9(50%) followed by cardiac arrest 6 (6.33%). In conclusion we can say clinical characteristics are more or less similar but those who have reduced ejection fraction with comorbidities are very prone to develop cardiac arrhythmia causing sudden cardiac death in heart failure. J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 192-198